Effective Strategies in Chinese Language Learning: Improving Speaking Ability with Picture Media for Elementary Students at Universitas Sebelas Maret - Nurhaliza, Risty Fahira; Lituhayu, Nindita Swasti; Murtadhoh, Nuzulul Luthfi (Journal of Maobi, 2024)
Chinese is one of the difficult languages to learn, especially for foreign speakers. Therefore, research was conducted to find an easy and effective way to learn Chinese speaking. This study focuses on elementary level students at Sebelas Maret University, examining how effective strategies, specifically the use of picture media, can improve their Chinese speaking skills. The research method analyzes the effectiveness of visual media in increasing students learning motivation and understanding of the content. By collecting qualitative and quantitative data from learning sessions conducted with and without visual media, significant differences in students learning performance were found between the two methods. The study's theoretical contributions include advancing the understanding of visual media's role in language acquisition and providing a framework for integrating visual aids into language teaching. It confirms that visual media can significantly enhance students participation, understanding, and memorization of learning content. Additionally, the speaking skills of students who used the visual media learning method improved markedly compared to those who did not. This demonstrates that visual media is a beneficial strategy for Chinese language learning at the elementary level, offering practical insights for teachers to enhance the efficiency of the learning process and improve student outcomes.